Mitochondrial Dynamics in Heart Disease - Dorn, Gerald W (2012)
Mitochondrial fission and fusion have been observed, and their importance revealed, in almost every tissue and cell type except adult cardiac myocytes. As each human heart is uniquely dependent upon mitochondria to generate massive amounts of ATP that fuel its approximately 38 million contractions per year, it seems odd that cardiac myocytes are the sole exception to the general rule that mitochondrial dynamism is important to function. Here, I briefly review the mechanisms for mitochondrial fusion and fission and examine current data that dispel the previous notion that mitochondrial fusion is dispensable in the heart. Rare and generally overlooked examples of cardiomyopathies linked either to naturally-occurring mutations or to experimentally-induced mutagenesis of mitochondrial fusion/fission genes are described. New findings from genetically targeted Drosophila and mouse models wherein mitochondrial fusion deficiency has specifically been induced in cardiac myocytes are discussed.